Numerical Simulation Analysis and Experimental Research on Damping Performance of a Novel Magnetic Fluid Damper - Wenrong Yang; Dejie Wei; Jianzheng Su; Xiaorui Yang; Qingxin Yang (Advances in Materials Science and Engineering)
Considering the low-frequency and large-amplitude vibration characteristics of the high-rise structure, a tuned magnetic fluid rolling-ball damper is proposed to suppress the vibration of the structure. By adjusting the external magnetic field to control the natural rolling frequency of the ball, the purpose of tuning vibration reduction is achieved. Firstly, the working principle of the damper is theoretically analysed, a three-dimensional (3D) magnetic-fluid-solid multiphysical field coupling mathematical model of the damper is established and the governing equations of multiphysical field coupling are derived. Secondly, the magnetic field distribution and operating characteristics of the damper are simulated and analysed. Finally, the effectiveness of the model is verified by experiments, and the damping performance of the damper with two kinds of magnetic fluid is tested and compared. The results show that the magnetic-fluid-solid multiphysical field coupling model can accurately simulate the working characteristics of the damper. The maximum damping force of the damper is about 12% of the elastic force of the structure, which can increase the damping ratio of the structure by about two times, effectively reduce the vibration response time, and suppress the vibration of the high-rise structure.